Strengthening of Social Cohesion in the Practice of Liké Geleng among the Aneuk Jamè Ethnic Group in Aceh - Bustami Abubakar; Ikhwan Ikhwan; Sugiarso Sugiarso (JSW (Jurnal Sosiologi Walisongo), 2021)
Liké geleng is a practice of traditions among the Aneuk Jamè ethnic group in Aceh. The implementation of Liké geleng tradition consisted of many traditions included the commemoration of Maulid Nabi. This study discusses the implementation of Liké geleng and its relationship with strengthening social cohesion among the Aneuk Jamè ethnic group in Kampung Balai, Samadua, South Aceh. This research objective is to explore the traditions within the Liké geleng and how the implementation of the traditions among the Aneuk Jamè ethnic community. The informants consisted of religious leaders, traditional leaders, women leaders, and the community involved in carrying out the Maulid Nabi memorial in the village. Applying the method of qualitative research, the results of the study showed that the implementation of Liké geleng among the Aneuk Jamè ethnic group as an activity in commemoration of the Maulid Nabi Muhammad is an activity that can strengthen social cohesion in the community. This is indicated by the development of closer friendship and kinship, increasingly frequent social interactions, and stronger cooperation between communities. This result proved that tradition may strengthen social cohesion by doing the tradition together.